Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F; Nabais, C; García-González, I; Cherubini, P; Gutiérrez, E; Freitas, H (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Relationships between climate and double rings in Quercus ilex from northeast Spain - Campelo, F; Gutiérrez, E; Ribas, M; Nabais, C; Freitas, H (Canadian Journal of Forest Research, 2007)
The influence of climatic factors on tree-ring width and the formation of double rings was studied in Quercus ilex L. growing in a coppice stand left unmanaged for 22 years. Ten trees were felled and discs were taken every 30 cm from bole and dominant branches. Dendrometer bands were installed on 10 nearby trees and the data recorded were used to confirm the accuracy of our tree-ring identification. They were also used to relate the seasonal radial growth pattern to double-ring formation. Double rings were frequent and occurred consistently along the stem. Two types of double rings could be recognized according to their width: type I, with the extra growth band accounting for approximately 50% of the tree ring; and type II, with a narrow extra growth band. Type I double rings were formed when approximately 1/2 of the growing-season precipitation occurred during the second growth period of the season and after the summer drought. Type II double rings occurred when approximately 1/3 of the precipitation in the growing season occurred after the summer drought. The formation of double rings was triggered by rainfall in summer and the extra growth-band width was related to summer and autumn environmental conditions. Double rings in Q. ilex can potentially be used in dendroclimatological studies, as they are formed in response to climatic conditions within the growing season.
doi: 10.1139/X07-050
Keywords: chronology (voyant); double rings; Drought; growth pattern; growth rings; Precipitation; Quercus ilex

Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica - GARCÍA, L V; POLO, A; Maltez-Moro, S; Gutiérrez, E; PÉREZ-RAMOS, I M; JORDÁN, A; MARTÍNEZ-ZAVALA, L; MARAÑÓN, T (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.
Keywords: acumulación de hojarasca; densidad cubierta vegetal leñosa; dosel leñoso; Quercus (voyant); suelo

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A; Molinas, M; Gutiérrez, E (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.